People on the move: migration and mobility in the European Union - Batsaikhan, Uuriintuya; Darvas, Zsolt; Raposo, Inês Gonçalves (Brussels, 2018)
"Migration is one of the most divisive policy topics in today’s Europe. In this publication, the authors assess the immigration challenge that the EU faces, analyse public perceptions, map migration patterns in the EU and review the literature on the economic impact of immigration to reflect on immigration policies and the role of private institutions in fostering integration."